Final Analysis of the Prevention of Early Menopause Study (POEMS)/SWOG Intergroup S0230. (27th October 2018) - Moore, Halle C F; Unger, Joseph M; Phillips, Kelly-Anne; Boyle, Frances; Hitre, Erika; Moseley, Anna; Porter, David J; Francis, Prudence A; Goldstein, Lori J; Gomez, Henry L; Vallejos, Carlos S; Partridge, Ann H; et al.
Abstract: Premature menopause is a serious long-term side effect of chemotherapy. We evaluated long-term pregnancy and disease-related outcomes for patients in S0230/POEMS, a study in premenopausal women with stage I–IIIA estrogen receptor–negative, progesterone receptor–negative breast cancer to be treated with cyclophosphamide-containing chemotherapy. Women were randomly assigned to standard chemotherapy with or without goserelin, a gonadotropin-releasing hormone agonist, and were stratified by age and chemotherapy regimen. All statistical tests were two-sided. Of 257 patients, 218 were eligible and evaluable (105 in the chemotherapy + goserelin arm and 113 in the chemotherapy arm). More patients in the chemotherapy + goserelin arm reported at least one pregnancy vs the chemotherapy arm (5-year cumulative incidence = 23.1%, 95% confidence interval [CI] = 15.3% to 31.9%; and 12.2%, 95% CI = 6.8% to 19.2%, respectively; odds ratio = 2.34; 95% CI = 1.07 to 5.11; P = .03). Randomization to goserelin + chemotherapy was associated with a nonstatistically significant improvement in disease-free survival (hazard ratio [HR] = 0.55; 95% CI = 0.27 to 1.10; P = .09) and overall survival (HR = 0.45; 95% CI = 0.19 to 1.04; P = .06). In this long-term analysis of POEMS/S0230, we found continued evidence that patients randomly assigned to receive goserelin + chemotherapy were not only more likely to avoid premature menopause, but were also more likely to become pregnant without adverse effect on disease-related outcomes.